Glass ceramics and methods of making glass ceramics

By preparing microcrystalline glass containing lithium, specific elements M, phosphorus, oxygen, boron, and silicon, the problem of low lithium ion conductivity of oxide-based solid electrolytes is solved, and a microcrystalline glass with high lithium ion conductivity is achieved, which is suitable for solid electrolytes of lithium ion batteries.

CN119894840APending Publication Date: 2025-04-25AGC INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380067003.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-20
Filing Date
2023-09-08
Publication Date
2025-04-25

Smart Images

  • Figure CN119894840A_ABST
    Figure CN119894840A_ABST
Patent Text Reader

Abstract

Provided is a glass ceramic having lithium (Li), an element M, phosphorus (P), oxygen (O), and at least one element selected from boron (B) and silicon (Si), the element M containing at least one element selected from zirconium (Zr), hafnium (Hf), tin (Sn), samarium (Sm), niobium (Nb), tantalum (Ta), tungsten (W) and molybdenum (Mo), the maximum peak occurring in the range of 2 [theta] = 20-30 degrees in the X-ray diffraction pattern of the glass ceramic being derived from a monoclinic structure, and the maximum peak occurring in the range of 2 [theta] = 20-30 degrees in the X-ray diffraction pattern of the glass ceramic being derived from at least one element selected from boron (B) and silicon (Si). The half-peak width of the maximum peak is 0.10 degrees or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to glass-ceramics and a method for manufacturing glass-ceramics. Background Art

[0002] In recent years, all-solid-state lithium-ion batteries have attracted attention from the perspectives of safety and high-speed charging. Since all-solid-state lithium-ion batteries use solid electrolytes instead of liquid electrolytes, they have the characteristics of no leakage and other problems and high safety.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: International Publication No. 2021 / 251405 Summary of the invention

[0006] Sulfide-based solid electrolytes have been known as solid electrolytes for lithium-ion batteries, but sulfide-based solid electrolytes have a problem in that they generate hydrogen sulfide when reacting with moisture in the atmosphere.

[0007] On the other hand, oxide-based solid electrolytes have higher environmental stability and are easier to handle than sulfide-based solid electrolytes, and are therefore considered to be promising materials as solid electrolytes for all-solid-state batteries.

[0008] However, current oxide-based solid electrolytes have problems with lithium ion conductivity. For example, the lithium ion conductivity of current oxide-based solid electrolytes is more than one order of magnitude lower than that of conventional sulfide-based solid electrolytes.

[0009] It should be noted that a lithium ion conductive oxide containing amorphous LiTa2PO8 that addresses this problem is disclosed in Patent Document 1. However, even in this material, it cannot be said that its lithium ion conductivity is not inferior to that of a sulfide-based solid electrolyte.

[0010] Therefore, there is still a need for oxide-based solid electrolytes with high lithium ion conductivity.

[0011] The present invention was completed in view of such background, and the object of the present invention is to provide a microcrystalline glass with high lithium ion conductivity that can be used as a solid electrolyte for lithium ion batteries. In addition, the object of the present invention is to provide a method for manufacturing microcrystalline glass with such high lithium ion conductivity.

[0012] In the present invention, a microcrystalline glass is provided, comprising:

[0013] lithium (Li), element M, phosphorus (P) and oxygen (O), and at least one selected from boron (B) and silicon (Si),

[0014] The element M includes at least one selected from zirconium (Zr), hafnium (Hf), tin (Sn), samarium (Sm), niobium (Nb), tantalum (Ta), tungsten (W) and molybdenum (Mo),

[0015] In the X-ray diffraction pattern of the glass-ceramics, the maximum peak generated in the range of 2θ=20° to 30° is derived from the monoclinic crystal structure, and the half-value width of the maximum peak is 0.10° or more.

[0016] In addition, the present invention provides a method for manufacturing microcrystalline glass, comprising the following steps:

[0017] (1) mixing a first raw material and a second raw material to prepare a mixed powder, wherein the first raw material comprises lithium (Li), an element M, phosphorus (P) and oxygen (O), the second raw material comprises at least one selected from boron (B) and silicon (Si), and the element M comprises at least one selected from zirconium (Zr), hafnium (Hf), tin (Sn), samarium (Sm), niobium (Nb), tantalum (Ta), tungsten (W) and molybdenum (Mo);

[0018] (2) heating the mixed powder to a temperature of 1200° C. to 1650° C. to obtain a melt;

[0019] (3) cooling the melt to form a glass sheet containing seed crystals;

[0020] (4) crushing the glass sheet to obtain a glass material containing the seed crystal;

[0021] (5) The glass material is heated to a temperature above the crystallization temperature to form glass-ceramics.

[0022] The present invention can provide a glass-ceramic with high lithium ion conductivity that can be suitably used as a solid electrolyte for lithium ion batteries. In addition, the present invention can also provide a method for producing the glass-ceramic with such high lithium ion conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a flowchart schematically showing an example of a method for producing glass-ceramics according to one embodiment of the present invention.

[0024] Figure 2 This is a diagram showing an example of an X-ray diffraction pattern of glass-ceramics (sample 1) according to one embodiment of the present invention.

[0025] Figure 3 This is a diagram showing an example of an X-ray diffraction pattern of glass-ceramics (sample 2) according to another embodiment of the present invention.

[0026] Figure 4 This is a diagram showing an example of an X-ray diffraction pattern of glass-ceramics (sample 4) according to another embodiment of the present invention.

[0027] Figure 5 It is a diagram showing the EDX element mapping result of the glass-ceramics (sample 1) according to one embodiment of the present invention.

[0028] Figure 6 It is a diagram showing the EDX element mapping result of the glass-ceramics (sample 2) according to another embodiment of the present invention.

[0029] Figure 7 It is a diagram showing the EDX element mapping result of the glass-ceramics (sample 22) according to the comparative example. DETAILED DESCRIPTION

[0030] Hereinafter, one embodiment of the present invention will be described.

[0031] In one embodiment of the present invention, a glass-ceramic is provided, comprising:

[0032] lithium (Li), element M, phosphorus (P) and oxygen (O), and at least one selected from boron (B) and silicon (Si),

[0033] The element M includes at least one selected from zirconium (Zr), hafnium (Hf), tin (Sn), samarium (Sm), niobium (Nb), tantalum (Ta), tungsten (W) and molybdenum (Mo),

[0034] In the X-ray diffraction pattern of the glass-ceramics, the maximum peak generated in the range of 2θ=20° to 30° is derived from the monoclinic crystal structure, and the half-value width of the maximum peak is 0.10° or more.

[0035] In the present application, hereinafter, Li, the element M, P, and O are also collectively referred to as a “first component”, and B and Si are also collectively referred to as a “second component”.

[0036] The first component is mainly a component that helps crystallization in the manufacturing process of microcrystalline glass (described in detail later), and the "second component" is mainly a component that helps glass formation in the manufacturing process of microcrystalline glass (described in detail later). It should be noted that these divisions are for convenience and are not absolute. For example, Li, P and O can exist in both the "first component" and the "second component".

[0037] As described above, an oxide-based solid electrolyte having high lithium ion conductivity is required.

[0038] In this regard, one embodiment of the present invention provides a glass-ceramic having a significantly high lithium ion conductivity, for example, exceeding 0.40 mS / cm. Therefore, when the glass-ceramic according to one embodiment of the present invention is applied to a solid electrolyte of a lithium ion battery, a high lithium ion conductivity can be obtained.

[0039] The glass-ceramics of one embodiment of the present invention has a crystalline portion and has a characteristic that a peak appears in the range of 2θ=20° to 30° in an X-ray diffraction pattern. In particular, the maximum peak that appears in the range of 2θ=20° to 30° corresponds to a monoclinic structure of an oxide containing a "first component". In addition, the half-peak width of this maximum peak is greater than 0.10°.

[0040] The half-value width of the maximum peak is preferably in the range of 0.10° to 0.50°, more preferably in the range of 0.10° to 0.30°, further preferably in the range of 0.10° to 0.20°, particularly preferably in the range of 0.10° to 0.17°, and most preferably in the range of 0.10° to 0.15°.

[0041] Due to the crystalline components having the monoclinic structure, the glass-ceramics according to one embodiment of the present invention has high lithium ion conductivity.

[0042] In addition, the glass-ceramics according to one embodiment of the present invention has a crystal part and a grain boundary part. The crystal part may contain at least one of Si and B in addition to Li, element M, P, and O. In addition, the grain boundary part may contain P and O.

[0043] (Other characteristics of glass-ceramics according to one embodiment of the present invention)

[0044] Next, other features of the glass-ceramics according to one embodiment of the present invention (hereinafter referred to as “first glass-ceramics”) will be described.

[0045] (composition)

[0046] As described above, the first glass-ceramics has the element M, and the element M may contain at least one selected from the group consisting of Zr, Hf, Sn, Sm, Nb, Ta, W, and Mo. In particular, the element M preferably contains Ta.

[0047] The Li content relative to the total of cations contained in the first microcrystalline glass is preferably in the range of 29.0 atomic % to 44.5 atomic %, more preferably in the range of 29.5 atomic % to 42.0 atomic %, further preferably in the range of 30.0 atomic % to 39.0 atomic %, particularly preferably in the range of 30.5 atomic % to 36.0 atomic %, and most preferably in the range of 31.0 atomic % to 33.0 atomic %.

[0048] In addition, relative to the total amount of cations contained in the first microcrystalline glass, the content of element M is preferably 25.5 atomic % to 45.0 atomic %, more preferably 30.0 atomic % to 44.0 atomic %, further preferably 35.0 atomic % to 43.0 atomic %, particularly preferably 38.0 atomic % to 42.0 atomic %, and most preferably 40.0 atomic % to 41.0 atomic %.

[0049] In addition, relative to the total amount of cations contained in the first microcrystalline glass, the P content is preferably 13.0 atomic % to 22.5 atomic %, more preferably 15.0 atomic % to 22.0 atomic %, further preferably 17.0 atomic % to 21.5 atomic %, particularly preferably 19.0 atomic % to 21.0 atomic %, and most preferably 20.0 atomic % to 20.5 atomic %.

[0050] In addition, when B is contained, the B content is preferably 2.5 atomic % to 13.0 atomic % relative to the total of cations contained in the first microcrystalline glass, more preferably 3.0 atomic % to 11.0 atomic %, further preferably 3.5 atomic % to 9.0 atomic %, particularly preferably 4.0 atomic % to 7.0 atomic % and most preferably 4.5 atomic % to 5.5 atomic %.

[0051] Furthermore, when containing Si, the Si content is preferably 0.8 atomic % to 3.8 atomic %, more preferably 1.0 atomic % to 3.0 atomic %, further preferably 1.2 atomic % to 2.5 atomic %, particularly preferably 1.3 atomic % to 2.0 atomic %, and most preferably 1.4 atomic % to 1.7 atomic %.

[0052] Moreover, the glass-ceramics according to one embodiment of the present invention may have a glass transition temperature Tg in the range of 600°C to 800°C.

[0053] As described above, the glass-ceramics according to one embodiment of the present invention may have a Li ion conductivity of 0.40 mS / cm or more at room temperature.

[0054] (Application example)

[0055] Since the first glass-ceramics exhibits high Li ion conductivity, it can be applied to various electrochemical devices such as all-solid-state batteries.

[0056] For example, the first glass-ceramics may be suitably used as a solid electrolyte (layer or sheet) in various electrochemical devices. Or the first glass-ceramics may be suitably used as an electrode in various electrochemical devices.

[0057] (Method for producing glass-ceramics according to one embodiment of the present invention)

[0058] Next, refer to Figure 1 , an example of a method for manufacturing microcrystalline glass having the characteristics described above is described.

[0059] Figure 1 An example of a flow of a method for producing glass-ceramics according to one embodiment of the present invention is briefly shown.

[0060] like Figure 1 As shown, a method for manufacturing glass-ceramics according to one embodiment of the present invention (hereinafter referred to as “first method”) comprises:

[0061] (1) Step (S110) of mixing a first raw material containing Li, element M, P, and O with a second raw material containing at least one selected from B and Si to prepare a mixed powder;

[0062] (2) Step (S120), heating the mixed powder to a temperature of 1200°C to 1650°C to obtain a melt;

[0063] (3) step (S130), cooling the melt to form a glass sheet containing a seed crystal;

[0064] (4) step (S140), crushing the glass sheet to obtain a glass material including the seed crystal;

[0065] (5) Step (S150) of heating the glass material to a temperature higher than the crystallization temperature to form glass-ceramics.

[0066] Hereinafter, each step will be described in more detail.

[0067] (Process S110)

[0068] First, the raw materials are mixed to prepare a mixed powder.

[0069] The raw material includes a first raw material and a second raw material. The first raw material and the second raw material are preferably mixed in a powder state.

[0070] The first raw material contains Li, the element M, P, and O. In addition, the second raw material contains Si and B.

[0071] The first raw material is a raw material mainly required to constitute a crystal part in the glass-ceramics formed in the subsequent step S150. In addition, the second raw material is a raw material mainly required to constitute a glass part in the glass frit obtained in the step S140.

[0072] It should be noted that the division of the first raw material / the second raw material is for convenience and is not absolute. For example, Li, P and O may exist in both the "first raw material" and the "second raw material".

[0073] The first raw material contains the element M. As described above, the element M represents at least one element selected from Ta, Zr, Hf, Sn, Sm, Nb, Ta, W, and Mo.

[0074] For example, the first raw material may contain a compound and / or phosphate of Li. In addition, the first raw material may contain a compound and / or phosphate of element M. For example, when element M is tantalum (Ta), the first raw material may contain tantalum oxide.

[0075] On the other hand, the second raw material contains Si and B. The second raw material may further contain Li and / or P. For example, the second raw material may contain Si compounds, lithium salts of silicon oxide, phosphates of silicon, B oxides, lithium salts of boron oxide, and the like.

[0076] Furthermore, composite oxides thereof may also be used.

[0077] Furthermore, the first raw material and the second raw material may be composite oxides thereof.

[0078] Specifically, the following raw materials can be mentioned:

[0079] Li compounds: lithium carbonate (Li2CO3), lithium hydroxide and its hydrates (LiOH, LiOH.H2O), lithium oxide (Li2O), lithium sulfate (Li2SO4), lithium nitrate (LiNO3), lithium halides (LiF, LiCl, LiBr, LiI), lithium cyanide (LiCN), lithium citrate (Li3C6H5O7), lithium acetate (C2H3LiO2) and lithium oxalate (C2Li2O4);

[0080] Compounds of element M: Assuming M = Ta, tantalum oxide (Ta2O5, TaO2), tantalum halide (TaF5, TaCl5, Ta2Br 10 、Ta2i 10 ), tantalum oxide fluoride (TaFO2);

[0081] Phosphoric acid: H3PO4, H4P2O7, HPO3, P2O5;

[0082] Boric acid: H3BO3, HBO2, H2B4O7;

[0083] Si compounds: silicon dioxide (SiO2);

[0084] Composite oxides: lithium phosphate (LiPO3, Li3PO4, LiH2PO4), lithium silicate (Li2SiO3, Li4SiO4), lithium borate (LiBO2, Li3BO3, Li2B4O7), lithium tantalate (LiTaO3).

[0085] The mixed powder is prepared by thoroughly mixing the first raw material and the second raw material.

[0086] (Process S120)

[0087] Next, the prepared mixed powder is heated and melted in the air to form a molten material.

[0088] The melting temperature is in the range of 1200°C to 1650°C, preferably in the range of 1300°C to 1600°C, and more preferably in the range of 1400°C to 1500°C.

[0089] The melting time varies according to the amount of the mixed powder and the melting temperature, and can be, for example, less than 5 hours. The melting time can be, for example, less than 2 hours, less than 1 hour, or less than 30 minutes. The atmosphere for heating and melting is preferably air, and can also be under an oxidizing atmosphere or an inert gas atmosphere.

[0090] (Process S130)

[0091] Next, the melt is cooled.

[0092] The cooling method is not particularly limited. The crystallization from the melt follows a two-stage process of nucleation and crystal growth from the nucleus, but even if a seed crystal that becomes a nucleus is included, glass can be obtained by cooling faster than the crystal growth rate. For example, the melt can also be rapidly cooled by a roll-out machine, a press, or by dropping into a cooling liquid.

[0093] By cooling the melt, a glass sheet containing a seed crystal is formed. At this time, the seed crystal serving as the nucleus may be contained in the melt, or the nucleus may be generated from the melt.

[0094] The seed crystal includes an oxide of the element M. For example, when the element M is Ta, the seed crystal may be Ta2O x (x=3~5).

[0095] (Process S140)

[0096] Next, the obtained glass flakes are pulverized to form glass frits. The method for pulverizing the glass flakes is not particularly limited, and a conventional method such as a dry ball milling method can be used.

[0097] The average particle size of the glass frit is, for example, preferably in the range of 0.01 μm to 20 μm, more preferably in the range of 0.05 μm to 15 μm, further preferably in the range of 0.1 μm to 10 μm, particularly preferably in the range of 0.3 μm to 5 μm, and most preferably in the range of 0.5 μm to 3 μm.

[0098] Then, if necessary, the glass frit may be shaped into a molded body.

[0099] The molding method is not particularly limited. For example, the glass frit can be molded by cold isostatic pressing (CIP).

[0100] (Process S150)

[0101] Next, the formed or unformed glass frit is heat-treated.

[0102] The heat treatment temperature is a temperature equal to or higher than the crystallization temperature of the glass frit. For example, the heat treatment temperature is preferably in the range of 750°C to 1030°C, more preferably 750°C to 1000°C, further preferably 800°C to 980°C, and particularly preferably 850°C to 960°C.

[0103] The heat treatment time is not particularly limited, and is, for example, in the range of 0.5 to 80 hours, preferably 0.5 to 50 hours, more preferably 0.5 to 30 hours, further preferably 1 to 20 hours, and particularly preferably 2 to 10 hours.

[0104] By heat treatment, the seed crystals contained in the glass frit become nuclei and crystallize in the glass frit, thereby forming glass-ceramics having a crystal portion and a crystal grain boundary portion around it.

[0105] Assuming that M=Ta, the main crystal portion is a material in which a part of P in LiTa2PO8 is replaced by at least one of Si and B, and may also contain other crystals.

[0106] Through the above method, glass-ceramics according to one embodiment of the present invention can be manufactured.

[0107] Example

[0108] Hereinafter, examples of the present invention will be described. It should be noted that in the following description, Examples 1 to 4 and Examples 11 to 14 are examples, and Examples 21 to 23 are comparative examples.

[0109] (Example 1)

[0110] Glass-ceramics were produced using the following method.

[0111] (Production of glass sheets)

[0112] First, 24.11 g of tantalum oxide (Ta2O5, manufactured by Kanto Chemical, 3N5 high purity reagent) powder, 4.69 g of lithium metaphosphate (LiPO3, manufactured by Hakushin Chemical Research Institute), 0.67 g of lithium metaborate (LiBO2, manufactured by Fujifilm Wako Pure Chemicals, purity 99% or more), 0.40 g of lithium carbonate (Li2CO3, manufactured by Kanto Chemical, 3N5 high purity reagent) and 0.37 g of lithium metasilicate (Li2SiO3, manufactured by Strem Chemicals, purity 99%) were mixed to prepare a mixed powder. The mixed powder was mixed so that, in terms of atomic % of cations, lithium (Li) was 32.4%, tantalum (Ta) was 40.7%, phosphorus (P) was 20.3%, silicon (Si) was 1.5% and boron (B) was 5.0%.

[0113] Next, 30 g of the mixed powder was placed in a platinum container and melted by heating in the air. The melting temperature was set to 1450° C. and the melting time was set to 30 minutes. Then, the melt was stirred thoroughly with a platinum rod.

[0114] Next, the obtained melt was rapidly cooled by a roll-out machine, thereby obtaining about 27 g of a thin sheet of glass (hereinafter referred to as "glass sheet 1").

[0115] In the obtained glass piece 1, a white turbid part and a transparent part were confirmed to exist mixedly.

[0116] (Production of glass frit)

[0117] The glass frit was prepared by pulverizing the glass sheet 1 as follows.

[0118] 15 g of the glass flakes 1 and 250 g of stabilized zirconia balls having a diameter of 10 mm were placed in a 250 mL HDPE container and pulverized using a ball mill at a rotation speed of 94 rpm for 15 hours.

[0119] Thus, a white powder having an average particle size of about 1.0 μm (hereinafter referred to as “glass frit 1”) was obtained.

[0120] In addition, the average particle size of the glass frit is measured by a laser diffraction scattering method.

[0121] (Evaluation of glass frit)

[0122] Using glass frit 1, measurement of crystallization temperature and X-ray diffraction analysis were performed.

[0123] The crystallization temperature was measured using TG-DTA (thermogravimetric measurement-differential thermal analysis). The crystallization temperature of glass frit 1 was 782°C.

[0124] As a result of X-ray diffraction analysis using Cu-Kα rays, a peak derived from tantalum oxide (Ta 2 O 5 ) was observed, thereby confirming that the glass frit 1 contained seed crystals of tantalum oxide.

[0125] (Production of glass-ceramics)

[0126] Next, the obtained glass frit 1 is molded into a molded body.

[0127] 0.5 g of the glass frit 1 was placed in a superhard metal mold having a diameter of 10 mm, and a uniaxial pressing process was performed at a pressure of 40 MPa for 2 minutes.

[0128] Then, isostatic pressing was further performed at a pressure of 200 MPa to obtain a molded body having a diameter of 10 mm and a thickness of 1.5 mm. The obtained molded body is referred to as "Molded Body 1".

[0129] Next, the molded body 1 is heat treated by the following method.

[0130] First, the molded body 1 is placed on a platinum dish, and the platinum dish is heated to 950° C. at a heating rate of 300° C. / hour in the atmosphere. After being kept at 950° C. for 5 hours, the platinum dish is cooled to room temperature at a cooling rate of 300° C. / hour.

[0131] After the heat treatment, white glass-ceramics (hereinafter referred to as "sample 1") was obtained. The size of sample 1 was 9.0 mm in diameter x 1.3 mm in thickness.

[0132] (Example 2)

[0133] Glass frit (hereinafter referred to as "glass frit 2") was prepared by the same method as in Example 1. Furthermore, the molded body of the glass frit 2 was heat-treated to prepare glass-ceramics.

[0134] In Example 2, in the above-mentioned (production of glass sheets) process, the powders were mixed in such a manner that the atomic percentage of cations was 34.0% Li, 38.8% Ta, 19.4% P, 1.8% Si, and 6.1% B to prepare the mixed powder. In addition, in Example 2, in the (production of microcrystalline glass) process, the heat treatment temperature was set to 920° C. The other conditions were the same as those in Example 1.

[0135] After heat treatment of the molded body (referred to as "molded body 2"), a glass-ceramic having a white appearance (hereinafter referred to as "sample 2") was obtained.

[0136] In addition, when the crystallization temperature of glass frit 2 was measured similarly to the case of Example 1, the crystallization temperature was 784° C. In addition, the result of X-ray diffraction analysis of glass frit 2 confirmed that glass frit 1 contained seed crystals of tantalum oxide.

[0137] (Example 3)

[0138] Glass frit (hereinafter referred to as "glass frit 3") was prepared by the same method as in Example 1. Furthermore, the molded body of the glass frit 3 was heat-treated to prepare glass-ceramics.

[0139] In Example 3, in the above-mentioned (production of glass sheets) process, the powders were mixed in such a manner that the atomic percentage of cations was 36.7% of Li, 35.4% of Ta, 17.7% of P, 2.4% of Si, and 7.9% of B to prepare the mixed powder. In addition, in Example 3, in the (production of microcrystalline glass) process, the heat treatment temperature was set to 860° C. The other conditions were the same as those in Example 1.

[0140] After heat treatment of the molded body (referred to as "molded body 3"), a glass-ceramic having a white appearance (hereinafter referred to as "sample 3") was obtained.

[0141] In addition, when the crystallization temperature of glass frit 3 was measured similarly to the case of Example 1, the crystallization temperature was 714° C. In addition, the result of X-ray diffraction analysis of glass frit 3 confirmed that glass frit 1 contained seed crystals of tantalum oxide.

[0142] (Example 4)

[0143] Glass frit (hereinafter referred to as "glass frit 4") was prepared by the same method as in Example 1. Furthermore, the molded body of the glass frit 4 was heat-treated to prepare glass-ceramics.

[0144] In Example 4, in the above-mentioned step (production of glass sheet), the powders were mixed and prepared in such a manner that the atomic percentage of cations was 40.1% Li, 31.0% Ta, 15.5% P, 3.1% Si and 10.3% B. The other conditions were the same as those in Example 1.

[0145] After heat treatment of the molded body (referred to as "molded body 4"), a glass-ceramic having a white appearance (hereinafter referred to as "sample 4") was obtained.

[0146] In addition, when the crystallization temperature of glass frit 4 was measured similarly to the case of Example 1, the crystallization temperature was 729° C. In addition, the result of X-ray diffraction analysis of glass frit 4 confirmed that glass frit 1 contained seed crystals of tantalum oxide.

[0147] (Example 11)

[0148] Microcrystalline glass was produced by the same method as in Example 1 above.

[0149] In Example 11, the heat treatment temperature in the step (production of crystallized glass) was set to 785° C. The other conditions were the same as those in Example 1.

[0150] After the heat treatment of the molded body 1, a glass-ceramic having a white appearance was obtained (hereinafter referred to as "sample 11").

[0151] (Example 12)

[0152] Microcrystalline glass was produced by the same method as in Example 1 above.

[0153] In Example 12, in the step (production of crystallized glass), the heat treatment temperature was set to 1000° C. The other conditions were the same as those in Example 1.

[0154] After the heat treatment of the molded body 1, a glass-ceramic having a white appearance was obtained (hereinafter referred to as "sample 12").

[0155] (Example 13)

[0156] Microcrystalline glass was produced by the same method as in Example 1 above.

[0157] In Example 13, the heat treatment time at 950° C. was set to 30 hours in the step (production of microcrystalline glass). Other conditions were the same as those in Example 1.

[0158] After the heat treatment of the molded body 1, a glass-ceramic having a white appearance was obtained (hereinafter referred to as "Sample 13").

[0159] (Example 14)

[0160] Microcrystalline glass was produced by the same method as in Example 1 above.

[0161] In Example 14, the heat treatment time at 950° C. was set to 75 hours in the step (production of crystallized glass). Other conditions were the same as those in Example 1.

[0162] After the heat treatment of the molded body 1, a glass-ceramic having a white appearance was obtained (hereinafter referred to as "sample 14").

[0163] (Example 21)

[0164] Glass frit (hereinafter referred to as "glass frit 21") was prepared by the same method as in Example 1. Furthermore, a molded body of the glass frit 21 was heat-treated to prepare glass-ceramics.

[0165] In Example 21, in the above-mentioned (production of glass sheets) process, the powders were mixed in such a manner that the atomic percentage of cations was 44.6% Li, 25.4% Ta, 12.7% P, 4.0% Si and 13.3% B to prepare the mixed powder. In addition, in Example 21, in the (production of microcrystalline glass) process, the heat treatment temperature was set to 690° C. The other conditions were the same as those in Example 1.

[0166] After heat treatment of the molded body (referred to as "molded body 21"), a glass-ceramic having a white appearance (hereinafter referred to as "sample 21") was obtained.

[0167] In addition, when the crystallization temperature of the glass frit 21 was measured in the same manner as in Example 1, the crystallization temperature was 692° C. In addition, the result of X-ray diffraction analysis of the glass frit 21 confirmed that no crystals existed in the glass frit 21 .

[0168] (Example 22)

[0169] Glass-ceramics were produced using the following method.

[0170] (Preparation of LiTa2PO8 crystal powder)

[0171] Using a dry ball mill, 23.86 g of tantalum oxide (Ta2O5, manufactured by Kanto Chemical, 3N5 high-purity reagent) powder and 4.64 g of lithium metaphosphate (LiPO3, manufactured by Hakushin Chemical Research Institute) were mixed to prepare a mixed powder.

[0172] Next, the mixed powder was placed in a zirconia container and heated to 1170°C at a heating rate of 300°C / hour in the atmosphere. Then, the temperature was maintained for 6 hours and then cooled to room temperature at a cooling rate of 300°C / hour. After the heat treatment, a bulk product was recovered.

[0173] Then, the bulk product was pulverized by a dry ball mill to obtain a powder having an average particle size of 5.2 μm. Crystalline LiTa2PO8 was confirmed in the powder.

[0174] (Preparation of Li-containing borosilicate glass frit)

[0175] Mix 12.60 g of lithium borate (LiBO2, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity over 99%), 7.50 g of lithium carbonate (Li2CO3, manufactured by Kanto Chemical, 3N5 high-purity reagent) and 6.90 g of lithium metasilicate (Li2SiO3, manufactured by Strem Chemicals, purity 99%) to prepare a mixed powder (referred to as "mixed powder A").

[0176] Next, 27 g of the mixed powder A was added to a platinum container and melted by heating. The melting temperature was set to 1450° C. and the melting time was set to 30 minutes. Then, the melt was stirred thoroughly with a platinum rod.

[0177] Next, the obtained melt is rapidly cooled by the above-mentioned method, thereby obtaining a thin glass piece (hereinafter referred to as "glass piece 22").

[0178] The obtained glass sheet 22 is transparent.

[0179] Next, 15 g of the glass flakes 22 and 250 g of stabilized zirconia balls having a diameter of 10 mm were placed in a 250 mL HDPE container and pulverized using a ball mill at a rotation speed of 94 rpm for 15 hours.

[0180] Thus, a Li-containing borosilicate glass frit (hereinafter referred to as “glass frit 22 ”) having an average particle size of 1.0 μm was obtained.

[0181] In addition, when the crystallization temperature of the glass frit 22 was measured as in Example 1, the crystallization temperature was 370° C. In addition, the result of X-ray diffraction analysis of the glass frit 22 confirmed that there were no crystals in the glass frit 22 .

[0182] (Production of glass-ceramics)

[0183] Next, 9.5 g of the LiTa2PO8 crystal powder prepared as described above was mixed with 0.5 g of the glass frit 22 to obtain a mixture (hereinafter referred to as "mixture 22").

[0184] Then, the mixture 22 was molded into a molded body by the same method as in Example 1, and then the molded body was heat-treated to produce glass-ceramics. In Example 22, the heat treatment conditions for the molded body were 1050° C. and 24 hours.

[0185] Thus, a glass-ceramic having a white appearance (hereinafter referred to as “Sample 22”) was obtained.

[0186] (Example 23)

[0187] Glass-ceramics are produced by the following method.

[0188] (Production of glass sheets)

[0189] First, 23.45 g of lithium metaphosphate (LiPO3, manufactured by Hakushin Chemical Research Institute), 3.35 g of lithium metaborate (LiBO2, manufactured by Fujifilm Wako Pure Chemicals, purity 99% or more), 2.00 g of lithium carbonate (Li2CO3, manufactured by Kanto Chemical, 3N5 high purity reagent) and 1.85 g of lithium metasilicate (Li2SiO3, manufactured by Strem Chemicals, purity 99%) were mixed to prepare a mixed powder. The mixed powder was mixed so that the atomic percentage of cations was 54.7% lithium (Li), 34.3% phosphorus (P), 2.5% silicon (Si) and 8.5% boron (B).

[0190] Next, the mixed powder was placed in a platinum container and melted by heating. The melting temperature was set to 1450° C. and the melting time was set to 30 minutes. Then, the melt was stirred thoroughly with a platinum rod.

[0191] Next, the obtained melt was rapidly cooled by the above-mentioned method, thereby obtaining about 26 g of a thin sheet of glass (hereinafter referred to as "glass sheet 23").

[0192] In the obtained glass piece 23, it was confirmed that a white turbid part and a transparent part existed mixedly.

[0193] (Preparation of a mixture of glass frit and tantalum oxide powder)

[0194] Next, 12.28 g of tantalum oxide (Ta2O5, manufactured by Kanto Chemical, 3N5 high-purity reagent) powder was added to 3.00 g of glass flakes 23. 250 g of stabilized zirconia balls with a diameter of 10 mm were added to the mixture, and a 250 mL HDPE container was added to perform ball mill pulverization. The rotation speed was set to 94 rpm, and the pulverization time was 15 hours.

[0195] As a result, a white powder having an average particle size of about 1.2 μm (hereinafter referred to as “mixture 23”) was obtained.

[0196] (Production of glass-ceramics)

[0197] Then, the mixture 23 was molded into a molded body by the same method as in Example 1, and then the molded body was heat-treated to produce glass-ceramics. In Example 23, the heat treatment conditions for the molded body were 1050° C. and 24 hours.

[0198] Thus, a glass-ceramic having a white appearance (hereinafter referred to as “Sample 23”) was obtained.

[0199] Table 1 below summarizes the manufacturing conditions and the like of the samples manufactured in each example.

[0200]

[0201] (evaluate)

[0202] The following evaluations were carried out using each sample.

[0203] (X-ray diffraction analysis)

[0204] X-ray diffraction analysis of each sample was performed using Cu-Kα rays.

[0205] Figure 2 to Figure 4 An example of the obtained X-ray diffraction pattern is shown in FIG. Figure 2 The X-ray diffraction pattern obtained in Sample 1 is shown in FIG. Figure 3 The X-ray diffraction pattern obtained in Sample 2 is shown in FIG. Figure 4 The X-ray diffraction pattern obtained in Sample 4 is shown in FIG.

[0206] Depend on Figure 2It can be seen that in sample 1, the maximum peak generated in the range of 2θ=20° to 30° appears at 2θ=25.37°. This maximum peak is derived from the monoclinic structure of LiTa2PO8, and the half-peak width is 0.10°.

[0207] In addition, by Figure 3 It can be seen that the maximum peak generated in the range of 2θ=20° to 30° appears at 2θ=25.42° in sample 2. This maximum peak is derived from the monoclinic structure of LiTa2PO8, and the half-peak width is 0.12°.

[0208] In addition, by Figure 4 It can be seen that the maximum peak generated in the range of 2θ=20° to 30° appears at 2θ=25.35° in sample 4. This maximum peak originates from the monoclinic structure of LiTa2PO8, and the half-peak width is 0.15°.

[0209] (EDX analysis)

[0210] Elemental mapping of each sample was performed using an EDX analysis device.

[0211] Figure 5 An example of the EDX element mapping result of sample 1 is shown in FIG. Figure 5 It is known that Ta, Si, and B exist in the crystal grains of Sample 1. In addition, P and oxygen are found to exist in the crystal grain boundaries of Sample 1.

[0212] Figure 6 An example of the EDX element mapping results of sample 2 is shown in FIG. Figure 6 It is known that Ta, Si, and B exist in the crystal grains of Sample 2. In addition, P and oxygen are found to exist in the crystal grain boundaries of Sample 2.

[0213] Figure 7 An example of the EDX element mapping result of sample 22 is shown in FIG. Figure 7 It is found that in Sample 22, Ta and Si exist in the crystal grains, but B does not exist. In addition, B, P, and oxygen are found to exist in the grain boundaries of Sample 22.

[0214] (Determination of ionic conductivity)

[0215] The ionic conductivity of each sample was measured by the following method.

[0216] (AC impedance measurement)

[0217] Gold electrodes (5 mm in diameter) were formed on both sides of the microcrystalline glass sample by vapor deposition. Next, a measurement voltage of 20 mV was applied to the gold electrode, and the impedance of the glass sheet was measured by the AC impedance method. The measurement was performed using 4990EDMS-120K (manufactured by TOYO Corporation) at a measurement frequency of 100 Hz to 100 MHz. Using the equivalent circuit analysis software ZView software included with the device, the obtained impedance spectrum was fitted with an equivalent circuit to evaluate the ionic conductivity of lithium ions.

[0218] The measurement results are summarized in Table 2 below.

[0219]

[0220] As shown in Table 2, it can be seen that not very good ion conductivity was obtained in Samples 21 to 23. In contrast, high ion conductivity exceeding 0.40 mS / cm was confirmed in Samples 1 to 4 and Samples 11 to 14.

[0221] (Mode of the Invention)

[0222] The present invention includes the following aspects.

[0223] (Method 1)

[0224] A microcrystalline glass having:

[0225] lithium (Li), element M, phosphorus (P) and oxygen (O), and at least one selected from boron (B) and silicon (Si),

[0226] The element M includes at least one selected from zirconium (Zr), hafnium (Hf), tin (Sn), samarium (Sm), niobium (Nb), tantalum (Ta), tungsten (W) and molybdenum (Mo),

[0227] In the X-ray diffraction pattern of the glass-ceramics, the maximum peak generated in the range of 2θ=20° to 30° is derived from the monoclinic crystal structure, and the half-value width of the maximum peak is 0.10° or more.

[0228] (Method 2)

[0229] The glass-ceramics according to Embodiment 1, wherein the element M includes Ta.

[0230] (Method 3)

[0231] The glass-ceramics according to embodiment 1 or 2, wherein the glass-ceramics has crystals and grain boundaries.

[0232] At least one of B and Si exists in the above crystal.

[0233] (Method 4)

[0234] The glass-ceramics according to any one of aspects 1 to 3, wherein the ion conductivity at room temperature is 0.40 mS / cm or more.

[0235] (Method 5)

[0236] An electrochemical device comprising the glass-ceramics according to any one of Methods 1 to 4.

[0237] (Method 6)

[0238] The electrochemical device according to Embodiment 5, wherein the electrochemical device is an all-solid-state battery.

[0239] (Method 7)

[0240] A solid electrolyte for an electrochemical device, comprising the glass-ceramics according to any one of Methods 1 to 4.

[0241] (Method 8)

[0242] An electrode for an electrochemical device, comprising the glass-ceramics according to any one of aspects 1 to 4.

[0243] (Method 9)

[0244] The solid electrolyte according to embodiment 7 or the electrode according to embodiment 8, wherein the electrochemical device is an all-solid-state battery.

[0245] (Method 10)

[0246] A method for manufacturing glass-ceramics, comprising the following steps:

[0247] (1) mixing a first raw material and a second raw material to prepare a mixed powder, wherein the first raw material comprises lithium (Li), an element M, phosphorus (P) and oxygen (O), the second raw material comprises at least one selected from boron (B) and silicon (Si), and the element M comprises at least one selected from zirconium (Zr), hafnium (Hf), tin (Sn), samarium (Sm), niobium (Nb), tantalum (Ta), tungsten (W) and molybdenum (Mo);

[0248] (2) heating the mixed powder to a temperature of 1200° C. to 1650° C. to obtain a melt;

[0249] (3) cooling the melt to form a glass sheet containing seed crystals;

[0250] (4) crushing the glass sheet to obtain a glass material containing the seed crystal;

[0251] (5) The glass material is heated to a temperature above the crystallization temperature to form glass-ceramics.

[0252] This application claims the priority based on Japanese Patent Application No. 2022-148696 filed on September 20, 2022, and all the contents of the Japanese application are incorporated into this application by reference.

Claims

1. A glass-ceramic having: lithium (Li), element M, phosphorus (P) and oxygen (O), and at least one selected from boron (B) and silicon (Si), The element M contains at least one selected from zirconium (Zr), hafnium (Hf), tin (Sn), samarium (Sm), niobium (Nb), tantalum (Ta), tungsten (W) and molybdenum (Mo), In the X-ray diffraction pattern of the glass-ceramics, the maximum peak generated in the range of 2θ=20° to 30° is derived from the monoclinic crystal structure, and the half-value width of the maximum peak is 0.10° or more.

2. The glass-ceramic according to claim 1, wherein: The element M includes Ta.

3. The glass-ceramic according to claim 1, wherein: The glass-ceramic has crystals and grain boundaries. At least one of B and Si exists in the crystal.

4. The glass-ceramic according to claim 1, wherein: The ionic conductivity at room temperature is above 0.40 mS / cm.

5. An electrochemical device comprising the glass-ceramics according to claim 1.

6. The electrochemical device according to claim 5, wherein: The electrochemical device is an all-solid-state battery.

7. A solid electrolyte for an electrochemical device, comprising the glass-ceramics according to claim 1.

8. An electrode for an electrochemical device, comprising the glass-ceramics according to claim 1.

9. The solid electrolyte according to claim 7 or the electrode according to claim 8, wherein The electrochemical device is an all-solid-state battery.

10. A method for manufacturing glass-ceramics, comprising the following steps: (1) mixing a first raw material and a second raw material to prepare a mixed powder, wherein the first raw material contains lithium (Li), an element M, phosphorus (P) and oxygen (O), the second raw material contains at least one selected from boron (B) and silicon (Si), and the element M contains at least one selected from zirconium (Zr), hafnium (Hf), tin (Sn), samarium (Sm), niobium (Nb), tantalum (Ta), tungsten (W) and molybdenum (Mo); (2) heating the mixed powder to a temperature of 1200° C. to 1650° C. to obtain a melt; (3) cooling the melt to form a glass sheet containing seed crystals; (4) crushing the glass sheet to obtain glass material containing the seed crystal; (5) Heating the glass material to a temperature above the crystallization temperature to form glass-ceramics.

Citation Information

Patent Citations

  • Cell characteristic evaluation device

    JP2022148696A

  • Solid electrolyte material, solid electrolyte, production methods therefor, and all-solid-state battery

    WO2021251405A1